In-Air Evoked Potential Audiometry of Grey Seals (Halichoerus grypus) from the North and Baltic Seas - Ruser, A.; Dahne, M.; Sundermeyer, J.; Lucke, Klaus; Houser, D.; Finneran, J.; Driver, J.; Pawliczka, I.; Rosenberger, T.; Siebert, U. (Public Library of Science, 2014)
In-air anthropogenic sound has the potential to affect grey seal (Halichoerus grypus) behaviour and interfere with acoustic communication. In this study, a new method was used to deliver acoustic signals to grey seals as part of an in-air hearing assessment. Using in-ear headphones with adapted ear inserts allowed for the measurement of auditory brainstem responses (ABR) on sedated grey seals exposed to 5-cycle (2-1-2) tone pips. Thresholds were measured at 10 frequencies between 1–20 kHz. Measurements were made using subcutaneous electrodes on wild seals from the Baltic and North Seas. Thresholds were determined by both visual and statistical approaches (single point F-test) and good agreement was obtained between the results using both methods. The mean auditory thresholds were ≤40 dB re 20 µPa peak equivalent sound pressure level (peSPL) between 4–20 kHz and showed similar patterns to in-air behavioural hearing tests of other phocid seals between 3 and 20 kHz. Below 3 kHz, a steep reduction in hearing sensitivity was observed, which differed from the rate of decline in sensitivity obtained in behavioural studies on other phocids. Differences in the rate of decline may reflect influence of the ear inserts on the ability to reliably transmit lower frequencies or interference from the structure of the distal end of the ear canal.